Comparing health inequality in men and women: prospective study of mortality 1986-96. Issue 7245 (13th May 2000) - Sacker, Amanda; Firth, David; Fitzpatrick, Ray; Lynch, Kevin; Bartley, Mel
Abstract: Objectives: To study prospectively the differences in health inequality in men and women from 1986-96 using the Office for National Statistics' longitudinal study and new socioeconomic classification.To assess the relative importance of social class (based on employment characteristics) and social position according to the general social advantage of the household to mortality risk in men and women. Design: Prospective study. Setting: England and Wales. Subjects: Men and women of working age at the time of the 1981 census, with a recorded occupation. Main outcome measures: Mortality. Results: In men, social class based on employment relations, measured according to the Office for National Statistics' socioeconomic classification, was the most important influence on mortality. In women, social class based on individual employment relations and conditions showed only a weak gradient. Large differences in risk of mortality in women were found, however, when social position was measured according to the general social advantage in the household. Conclusions: Comparisons of the extent of health inequality in men and women are affected by the measures of social inequality used. For women, even those in paid work, classifications based on characteristics of the employment situation may give a considerable underestimate. The Office for National Statistics' new measure of socioeconomic position is useful for assessing health inequality in men, but in women a more important predictor of mortality is inequality in general social advantage of the household.